2004
DOI: 10.1097/01.shk.0000142253.31006.8c
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Proteases and Inflammatory Mediators in Peritoneal Fluid During Splanchnic Arterial Occlusion and Reperfusion

Abstract: Pancreatic enzymes in the ischemic intestine are involved in the production of in vivo inflammatory mediators. These mediators stimulate cells in the cardiovascular system during shock and initiate multiorgan failure. An important aspect that controls the extent of the inflammation is the dispersion of these mediators from the ischemic intestine. In the past, two pathways for dispersion of these inflammatory mediators have been identified, absorption into the intestinal venous circulation and uptake into the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The peri-Vaterian duodenum (PV-D) possesses an extraordinary rich autonomic duodenumpancreatic innervation; thus, gallstones, biliary sludge, and/or hemobilia migrating and impacting on the PV-D or endoscopic maneuvers can trigger autonomous arc reflexes (AARs) (3) that initiate the acute pancreatic neurogenic inflammation (3,4). This initial setting, in which there is an overstimulation of the receptors in the PV-D, inducing a sympathetic hypertone responsible for catecholaminic discharge by nerve endings in the pancreas causing microcirculatory disruption that will conclude in ischemia/reperfusion lesions (5) translated into the release of proinflammatory molecules (tumor necrosis factor !, interleukin [IL] 8, IL-6, and inducible nitric oxide synthase [iNOS]) (6, 7) together with leukocyte recruitment (8) that correlate with intracellular enzyme activation (2). The biliopancreatic duct outlet exclusionYclosed duodenal loops (BPDOE-CDLs) model that we have previously described and validated (3) mimics these circumstances.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The peri-Vaterian duodenum (PV-D) possesses an extraordinary rich autonomic duodenumpancreatic innervation; thus, gallstones, biliary sludge, and/or hemobilia migrating and impacting on the PV-D or endoscopic maneuvers can trigger autonomous arc reflexes (AARs) (3) that initiate the acute pancreatic neurogenic inflammation (3,4). This initial setting, in which there is an overstimulation of the receptors in the PV-D, inducing a sympathetic hypertone responsible for catecholaminic discharge by nerve endings in the pancreas causing microcirculatory disruption that will conclude in ischemia/reperfusion lesions (5) translated into the release of proinflammatory molecules (tumor necrosis factor !, interleukin [IL] 8, IL-6, and inducible nitric oxide synthase [iNOS]) (6, 7) together with leukocyte recruitment (8) that correlate with intracellular enzyme activation (2). The biliopancreatic duct outlet exclusionYclosed duodenal loops (BPDOE-CDLs) model that we have previously described and validated (3) mimics these circumstances.…”
Section: Introductionmentioning
confidence: 95%
“…Acute pancreatitis (AP) is a disorder that, depending on the concentration of inflammatory mediators found, first locally and then systemically, can progress to a severe form with high morbidity and mortality (1,2). The peri-Vaterian duodenum (PV-D) possesses an extraordinary rich autonomic duodenumpancreatic innervation; thus, gallstones, biliary sludge, and/or hemobilia migrating and impacting on the PV-D or endoscopic maneuvers can trigger autonomous arc reflexes (AARs) (3) that initiate the acute pancreatic neurogenic inflammation (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that peritoneal fluid from ACS serves as a primer of naïve neutrophils and monocytes [10]. It is well documented that peritoneal fluid can be reabsorbed into the systemic circulation, primarily via lymphatic conduits [18,19]. Given this data and evidence that peritoneal fluid is pro-inflammatory by representing a potential primer for naïve neutrophils, a potential mechanism for systemic effects of peritoneal fluid can be made, either as an initiator (i.e., intra-abdominal sepsis) or propagator of systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The permeability increases and, as a result, intestinal contents may leak across the mucosal barrier [7], [8]. After escape from the intestinal lumen, intestinal contents can be transported through the venous intestinal vasculature [9], [10], lymphatics [11], [12], or via the peritoneum into the systemic circulation [13], [14], and may be responsible for distant organ injury [12], [15]. While many studies have investigated the transport of material into the blood and lymphatics from the intestine, few have investigated the importance of the transmural permeability in mammalian species, a route that provides direct access to peripheral organs, despite its association with poor outcome and death [11], [14], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells in microvessels, and extravasated leukocytes are also potential sources of MMPs [24], [25]. If activated or released during ischemia, these enzymes could degrade the intestinal wall, enabling leakage of pro-inflammatory mediators derived from the lumen (proteases, bacteria, digested food particles) of the intestine into the peritoneum [13], [14], [26]–[29].…”
Section: Introductionmentioning
confidence: 99%